THE EVOLUTION OF TYPICAL IMAGES AND CHARACTERS IN THE NOVEL AN AMERICAN TRAGEDY WITHIN A SOCIO-HISTORICAL CONTEXT (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the evolution of typical images and characters in Theodore Dreiser’s novel An American Tragedy within a socio-historical and philosophical framework. Drawing on the principles of literary naturalism, the study analyzes how heredity, environment, and social forces shape the fate of the protagonist, Clyde Griffiths, and other key characters. Particular attention is paid to the concept of the “American Dream” as a dominant ideological construct and its destructive influence on individual consciousness and moral choice. The article explores the psychological, social, and ethical determinants of crime in the novel, emphasizing that Clyde’s tragedy represents not only a personal failure but also a systemic crisis of American capitalist society. Through an analysis of major and secondary characters, including female figures and institutional representatives, the study reveals Dreiser’s critique of social Darwinism, religious dogmatism, and the punitive justice system. The findings demonstrate that An American Tragedy functions simultaneously as a personal drama and a socio-historical document, exposing the inherent contradictions of American society in the early twentieth century.